Analisis Dinamika Kepemimpinan Agile Dan Kapasitas Diri Dalam Membentuk Budaya Kerja dan Kinerja Pegawai: Studi Kasus Pada Kantor Syahbandar Kalimantan Selatan - Faisal Fattah; Megawaty Megawaty; Rachman Suwandaru (Movere Journal, 2026)
The increasingly dynamic and uncertain organizational environment requires public sector organizations to adopt adaptive leadership and strengthen employees’ psychological readiness, particularly in high-risk maritime public services. This study aims to explore the practices and experiences of agile leadership and employee self-efficacy in responding to operational dynamics and digital transformation through the Inaportnet system, to examine how work engagement contributes to job satisfaction, and to explain the role of job satisfaction as a psychological mechanism linking adaptive leadership, work engagement, and self-efficacy to public service performance. This study employs a qualitative approach with a case study design conducted at the Harbourmaster Office in South Kalimantan. Data were collected through in-depth interviews, non-participant observation, and document analysis, and were analyzed thematically. The findings indicate that agile leadership is perceived as responsive and context-driven leadership that supports employees in dealing with operational pressures and digital transformation. Self-efficacy emerges as a key psychological foundation enabling employees to adapt to complex job demands. Work engagement is experienced as a strong personal commitment to public service responsibilities and contributes to the formation of job satisfaction. Furthermore, job satisfaction functions as a psychological mechanism that allows employees to internalize leadership support, work engagement, and self-efficacy, thereby sustaining public service performance. This study contributes theoretically to public sector organizational behavior literature and provides practical implications for leadership development and human resource management in the maritime sector